Analysis, Implementation of Onli ANALISIS PEMBELAJARAN DARING (DALAM JARINGAN) PADA MASA COVID 19 DI SDN NEGERI 01 KARANGTENGAH KECAMATAN AMPELGADING KABUPATEN PEMALANG TAHUN 2021 - Nikmah Hidayah; Sunan Baedowi; Sukamto Sukamto (JURNAL SINEKTIK, 2021)
The background that drives this research is that SDN 01 Karangtengah learners still excel in the implementation of online learning during the Covid-19 pandemic in the Ampelgading regional elementary school level championship. The purpose of this study was to analyze the implementation of online learning during the Covid-19 pandemic class IV SDN 01 Karangtengah. In the results of interviews, questionnaires, and documentation obtained the results of research in the online learning process during the Covid-19 pandemic in SDN 01 Karangtengah has been carried out properly, teachers and learners have the facilities needed, online learning planning has been implemented well with the media, methods, online learning models in accordance with the characteristics of learners. Online learning encourages teachers to be more creative in teaching in addition to students are required to be more active in the implementation of online learning